The Impact of Social Pressure and Monetary Incentive on Cognitive Control - Ličen, Mina; Hartmann, Frank; Repovš, Grega; Slapničar, Sergeja (Frontiers in Psychology, 2016)
In this study, we compare the effects of two prominent organizational control mechanisms—monetary incentive and social pressure—on cognitive control. Cognitive control underlies the human ability to regulate thoughts and actions in the pursuit of behavioral goals. Previous studies show that monetary incentives can contribute to goal-oriented behavior via the activation of proactive control. There is, however, much less evidence on the effect of social pressure on cognitive control and task performance. In a within-subject experimental design, we tested 47 subjects performing the AX-CPT task to compare the activation of cognitive control modes under monetary incentive and social pressure beyond mere instructions to perform better. We find that social pressure and monetary incentive have similar effects as mere instructions on cognitive control. All three lead to a significant shift from a reactive to a proactive control mode and a similar improvement in task performance. Our findings suggest that social control mechanisms and monetary incentives provide similar behavioral effects in stimulating a proactive cognitive control mode and performance.